Surveillance Robot for Military Application (International Journal of Engineering and Computer Science, 2018)
This project presents a modern approach for surveillance at remote and border areas using multifunctional robot based on current IOT  used in defense and military applications. This robotic vehicle has ability to substitute the solider at border  area  t provide surveillance. The  robotic  vehicle  works  both   as autonomous and manually controlled vehicle using internet communication  medium.This multisensory   robot used to detect presence of enemy capture it in camera and  give  the  live  streaming  to  the  authorized  person Surveillance is major role while we workin on  border  area  for   this  there  is  robot  for surveillance  purpose.This paper presents a smart  surveillance  robot  for  military application by using  Raspberry  Pi  for  security purpose. An field Raspberr pi sends a wireless  command  which  is received  by Authorized  person on web  Page  and  accordingly  robot  moves. The Video  Streaming is  done using  Raspberry pi camera. The Raspberry pi programming is done in python language. The experimental result shows that the video streamed up to 15 frames per second.